The Impact of Non-interference Principle of ASEAN in Resolving Humanitarian Issues in Southeast Asia: A Case of Rohingya - Andi Pramawijaya Sar (FH IH 16 UMY 047, 2016)
The humanitarian crisis that happened in Myanmar has seized many attentions from the international community. Ethnic Rohingya has been the victim of the discrimination committed by the Myanmar Military Junta regime. Since 1962-2012, when General Ne Win staged a coup and took over the government and continued by Thein Sein, there had been more than 10,000 ethnic Rohingya killed and more than 200,000 had fled to neighboring countries. Various attempts have been made to solve the problems of inhumanity against the Rohingya. ASEAN as a regional organization that is in the Southeast Asian region has shown its serious concern in resolving the humanitarian crisis in Myanmar. The effort can be seen from the issuance of a statement to encourage the Government of Myanmar to stop the humanitarian crisis and serious attempt given by ASEAN to provide humanitarian assistance. However, today, the effort of ASEAN yet to show the progress because Rohingya still receive discrimination from the Government of Myanmar. This becomes a dilemma for ASEAN countries because in one side they want to solve the violence in Myanmar, while on the hand, the efforts collided with the principle of non-intervention which has been upheld by ASEAN and its member States. Such non-intervention principles have given a negative impact on any efforts to resolve various problems that arise nowadays, especially on the humanitarian issues. This study is a normative legal research with Statute and Case Approaches. This study analyzes the impact of non-interference principle of ASEAN in resolving the humanitarian issues in Southeast Asia. The results show that the non-interference principle maintained by ASEAN should be reconsidered as a tool to resolve the humanitarian issues that happened in Southeast Asia. Keywords: Non-interference Principle, Humanitarian Crisis, ASEAN, Rohingya